A Room of One's Own - Woolf, Virginia; Edited and Compiled by Prof. Munawar Ali Malik (Lahore New Kitab Mahal, 2008)
Why is it that men, and not women, have always had power, wealth, and fame? Woolf cites the two keys to freedom: fixed income and one's own room. Foreword by Mary Gordon.
Include Chronology
Keywords: Woolf, Virginia, 1882-1941 -- Women -- Great Britain -- Feminism -- British literature